2018
DOI: 10.1111/pcmr.12704
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 regulates a mitochondrial transcription program by modulating MITF

Abstract: FBXW7 is well characterized as a tumor suppressor in many human cancers including melanoma; however, the mechanisms of tumor-suppressive function have not been fully elucidated. We leveraged two distinct RNA sequencing datasets: human melanoma cell lines (n = 10) with control versus silenced FBXW7 and a cohort of human melanoma tumor samples (n = 51) to define the transcriptomic fingerprint regulated by FBXW7. Here, we report that loss of FBXW7 enhances a mitochondrial gene transcriptional program that is depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…FBXW7 downregulation is, however, not always followed by a substantial increase in the levels of its target proteins as shown for MCL‐1 in melanoma cells . More recently, it has been evidenced that loss of FBXW7 cooperates with BRAF V600E in melanomagenesis, and enhances the mitochondrial metabolic program by modulating MITF protein levels in melanoma cells …”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 downregulation is, however, not always followed by a substantial increase in the levels of its target proteins as shown for MCL‐1 in melanoma cells . More recently, it has been evidenced that loss of FBXW7 cooperates with BRAF V600E in melanomagenesis, and enhances the mitochondrial metabolic program by modulating MITF protein levels in melanoma cells …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FBXW7 was also found to regulate the oncogene MITF in melanoma. In vitro silencing of FBXW7 in melanoma considerably enhanced MITF/PGC-1 signaling contributing to the augmentation of mitochondrial transcription program and may result in poor outcomes for the patients [163] (Table 1).…”
Section: Deregulation Of Fbxw7 In Different Types Of Cancermentioning
confidence: 99%
“…However, an increased reduction in the cell survival ratio was higher in the SNU-C5/WT cells than in the SNU-C5/5FUR cells (Figure 1A). Recent studies have suggested that PGC-1α enhances the mitochondrial energy metabolism and biogenesis in melanoma, colorectal cancer, and endometrial carcinoma [24,25,26]. Moreover, PGC-1α is related to the drug resistance that occurs in ovarian cancer cells [27].…”
Section: Resultsmentioning
confidence: 99%